Distribution and accumulation of heavy metals in Red Cedar (Cedrela odorata) wood seedling grown in dumpsite soil - O.O. Akintola; I.A. Bodede (Journal of Applied Sciences and Environmental Management, 2019)
: Recent technological advancements in industrialization and urbanization process have led to release of toxic contaminants like heavy metals in the environment. This study assessed the ability of Cedrela odorata to  accumulate and distribute heavy metals such as Cu, Pb, Zn, Cd and Co in their roots and shoots planted in dumpsite soil by determining the  distribution factors and enrichment coefficients between soils and plant parts. Heavy metal concentrations (mg/kg) before planting were Cu (48.01-356.71), Pb (28.42-26.48), Zn (39.99- 437.88), Cd (0.69-9.59) and Co (16.88-29.22) while their concentrations after planting were Cu  (8.12-226.56), Pb (11.22-227.41), Zn (7.66-321.51), Cd (0.31-4.78) and Co (3.21-14.11). Heavy metal concentrations (mg/kg) in roots were Cu (9.93-20.11), Pb (7.26-15.21), Zn (9.05-22.35), Cd (0.11-0.99) and Co (4.56-6.11) and their concentration shoots of the plant were Cu (18.01-35.22), Pb (9.01-17.51), Zn (18.66-37.86), Cd (0.15-1.32) and Co (6.45-8.01). Enrichment coefficients and distribution factors were 0.1-1.21 and 1.29- 2.08 respectively. Heavy metal concentrations in dumpsite soil were found to be greater than control soil.The reductionobserved in concentrations of heavy metals in soils after planting indicated their enrichment in the plant tissues. Values of enrichment coefficients and distribution factors indicated the potential of Cedrela odorata as phytoextractor plant. This study has further proven the efficacy and ability of Cedrela odorata to accumulate and distribute heavy metals in its tissue parts. Thus Cedrela odorata seedlings can be used to clean or rehabilitate soils that are contaminated with the studied heavy metals.